2021
DOI: 10.1007/s10787-021-00847-2
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccines and decreased transmission of SARS-CoV-2

Abstract: A massive COVID-19 vaccination campaign is underway worldwide. Epidemiological data from studies indicate excellent efficacy and safety profile for COVID-19 vaccines. However, there are few data from studies on the effect of decreasing the probability of infection of vaccinated subjects compared to unvaccinated subjects. In this short communication, we describe some evidence on this important and current topic providing useful personal reflections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(111 citation statements)
references
References 28 publications
0
87
0
3
Order By: Relevance
“…COVID-19 infection is straight implicated in neurological invasion through diverse possible pathway as hypoxia brain injury, direct brain infection, autoimmune demotion, ACE2 pathway alteration, leading to impairments in cognition and neurogenesis ( Xiong et al, 2020 ; Di Carlo et al, 2021 ; Marin and Kipnis, 2013 ; Montemurro, 2021 ). We are extremely convinced of the usefulness of vaccination and epidemiological data from several studies indicated an excellent efficacy and safety profile for COVID-19 vaccines ( Vitiello et al, 2021 ). However, while the benefits of the COVID-19 vaccines far outweigh the risks, side effects continue to be reported, some of which are common, such as headache ( Sekiguchi et al, 2021 ) and others are much rarer ( Chan et al, 2022 ; Lazaro et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 infection is straight implicated in neurological invasion through diverse possible pathway as hypoxia brain injury, direct brain infection, autoimmune demotion, ACE2 pathway alteration, leading to impairments in cognition and neurogenesis ( Xiong et al, 2020 ; Di Carlo et al, 2021 ; Marin and Kipnis, 2013 ; Montemurro, 2021 ). We are extremely convinced of the usefulness of vaccination and epidemiological data from several studies indicated an excellent efficacy and safety profile for COVID-19 vaccines ( Vitiello et al, 2021 ). However, while the benefits of the COVID-19 vaccines far outweigh the risks, side effects continue to be reported, some of which are common, such as headache ( Sekiguchi et al, 2021 ) and others are much rarer ( Chan et al, 2022 ; Lazaro et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The vaccine is another effective tool for controlling infectious disease transmission ( Duijzer et al, 2018 ; Lin et al, 2020 ). The studies showed that the viral load of the C-19 virus in vaccinated patients is approximately one-third of that of unvaccinated patients ( Levine-Tiefenbrun et al, 2021 ; Vitiello et al, 2021 ). This factor reduces people's susceptibility to C-19 infection ( ) accordingly.…”
Section: Implementation and Evaluationmentioning
confidence: 99%
“…The more mutations that occur, the more likely it is that variants will appear. Vaccines are able to decrease the viral load in case of infection, thereby reducing the number of reproduction cycles of the virus by decreasing the possibility of new mutations and the emergence of new variants [ 27 , 28 ].…”
Section: Covid-19 Vaccines: Myths and Hesitancymentioning
confidence: 99%